Światopogląd jako styl. „Klucze Piotrowe” Rogera Peyrefitte’a w przekładzie Hanny Szumańskiej-Grossowej jako ogniwo tradycji - Kącka, Eliza (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article’s starting point is the consideration of selected works of Anatole France’s, André Gide’s and Guillaume Apolinaire’s, which over a hundred years ago would constitute a separate trend in the French pre-Vatican church. What differentiates the criticism of what is known as ultramontanism from the traditional anticlerical satire is the tone of persiflage, irony and theological erudition of almost grotesque proportions. In the 1950s, Roger Peyrefitte, a diplomat and a satirist of the Vatican, was an outstanding heir to this stylistic and thematic tradition. When translating his The Keys of St. Peter in 1959, Hanna Szumańska-Grossowa had to refer to the aforementioned author, who had lived half a century earlier, and work out a narrative of her own based on the achievements of J. Sten (Anatole France), Tadeusz Żeleński-Boy (André Gide) and Adam Ważyk (GuillaumeApollinaire).